MATERNAL DEATHS DUE TO ECLAMPSIA AND HELLP SYNDROME: A SYSTEMATIC REVIEW - Azkiya, Mayla (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Hypertensive disorders in pregnancy affect 10 of women and are a main cause of maternal morbidity and mortality worldwide. Preeclampsia, eclampsia, and Hemolysis, Elevated Liver Enzyme Levels and Low Platelet Levels (HELLP) syndrome are life-threatening hypertensive conditions that occur in pregnant woman. The aim: This study aims to show maternal deaths due to eclampsia and HELLP syndrome. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 39 articles, whereas the results of our search on SagePub brought up 106 articles. The results of the search conducted for the last year of 2013 yielded a total 25 articles for PubMed and 50 articles for SagePub. The result from title screening, a total 10 articles for PubMed and 22 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: The higher maternal age; prenatal history of hypertension and hypoproteinemia; and conditions requiring oral prednisolone, oral anticoagulants, and oral antiplatelets were identified as significant risk factors underlying critical obstetric bleeding, together with other obstetric complications. Prenatal hypertension may predispose patients to HELLP syndrome, eclampsia, and subsequent development of critical bleeding, but it may not predispose the patients to atonic bleeding.